Mugabe and the white African [videorecording (DVD)] - Thompson, Andrew; Bailey, Lucy (First Run Features, 2010)
"Family patriarch Mike Campbell is one of the few white farmers left in Zimbabwe since President Robert Mugabe began his violent land seizure program in 2000. Since then the country has descended into chaos, the economy brought to its knees by the reallocation of formerly white-owned farms to Mugabe cronies, who have no knowledge, experience or interest in farming. In 2008, after years of intimidation and threats to his family and farm, Campbell decides to take action. Unable to call upon the protection of any Zimbabwean authorities, he challenges Mugabe before an international court, [the Southern African Development Community Tribunal], charging him and his government with racial discrimination and human rights violations.."-- Publisher's website.